New Optimization Method of the MPPT Algorithm and Balancing Voltage Control of the Three-Level Boost Converter (TLBC) - Hassan Abouobaida; Said El Bied (International Journal of Applied Power Engineering (IJAPE), 2017)
This paper is dedicated to studying the control of the Three Level Boost Converters (TLBC) and the optimization method of Maximum Power Point Tracking (MPPT) based a variable step. The main objective of the optimization is to find a compromise between the response time and the amplitude of the oscillations around the optimal point. The nonlinear behavior of the TLBC is manifested by the presence of the disturbances. For reasons of simplicity of the control, a linearization based on the dynamic compensation of the disturbance is proposed. On the one hand, a cascaded MPPT algorithm and a simple linear regulator allow adjusting the inductance current and a maximum power operation of the wind system. On the other hand, a second linear regulator ensures balancing of the output voltages. The paper proposes a new approach to the optimization of the Inc-Cond MPPT. The suggested contribution consists of using an exponential function of the power derivative to develop a variable step. The adoption of the variable step size according to the dynamics of the wind system implies a compromise between the response time and the amplitude of the ripples around the optimal point. The simulation results showed that a variable step size, especially in transient conditions and during a very rapid climate change recover the optimum power point within a reasonable time and suitable amplitude of the oscillations. The results achieved in this study show the ability of the proposed approach to extract the maximum power according to the available wind speed while guaranteeing a better efficiency. The developed study is summarized by the following points: (a) modeling the wind conversion systems, (b) detailing the control approach of the TLBC and presenting the variable step method (c) presenting the simulations results and evaluating the perf.